Contribution to the Effectiveness and Efficiency of Kota Pari Village Communities in Increasing Sustainable Economic Growth and Creative Industry - Suwarno, Suwarno; Darmilisani, Darmilisani; Siregar, Mira Yosefa; Selviani, Putri (Journal of Community Research and Service, 2023)
The research team at Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency set out to answer the question, "How effective and efficient are the communities of Kota Pari Village in achieving sustainable economic growth and creative industries?" The primary objective of this study is to compare the creative industry's financial health before and after the implementation of community effectiveness and efficiency strategies to boost revenues. The research hypothesis is that the success and efficiency of the Kota Pari Village community contributes to the development of both the creative industries and long-term economic growth. The researcher's planned methodology.This technique is a quantitative one; specifically, it pertains to information describing the residents of Kota Pari Village, and more specifically, the homemakers there, and how they might improve their productivity and, ultimately, their earnings from the home-based business sector.Multiple linear regression analysis and statistical testing in SPSS version 25 were used to analyze the data. The study found that Efficiency (X1) significantly and positively affected Long-Term Economic Development (Y). Sustainable Economic Growth (Y) is positively and significantly affected by efficiency. The creative industries (Y2) benefit greatly from sustained economic growth (Y). The Creative Sector (Y2) benefits greatly from effectiveness (X1). The Creative Industries (Y2) benefit greatly from increased efficiency.